STUDENTS’ SELF-ASSESSMENT ON THEIR SPOKEN INTERACTION USING CEFR - Asdar Asdar (Proceedings Education and Language International Conference, 2017)
Assessment is one of the important parts in the teaching and learning process. For many students, assessment is something done to them by their teachers. But, students have to be involved in every assessment. Sometimes spoken interaction is scored by teachers but because of the limited time, teachers can ask students to assess their own spoken interaction. However, assessment conducted by the students still has many weaknesses even it is not trusted. This research studied about the students’ self assessment on their spoken interaction using CEFR. The researcher employed three instruments; self-assessment, a questionnaire, and open-ended questions. The participants of this study were 30 student teachers. The researcher gave the self-assessment form, a questionnaire and open-ended questions to them. The self-assessment form was used to find out their spoken interaction data while the questionnaire was used to find out their attitude toward self-assessment and open-ended questions were given to support their attitude toward self-assessment. It can be concluded that students’ self-assessment results were not too bad for new students and also they had good attitude toward self-assessment. Keywords: assessment, spoken interaction, speaking, attitude, self-confident